2005
DOI: 10.1248/bpb.28.1216
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Anticonvulsant Activity of 1-Substituted-7-Benzyloxy-4,5-dihydro-[1,2,4]triazolo[4,3-a]quinoline

Abstract: ؊1 and 13, respectively. The PI value of compound 4g was better than that of most marketed drugs. Structure-activity relationships are also described in this paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…Quinoline anticonvulsant compounds. (Table 1), with TD50 values of greater than 300 mg/kg which was better than most of the market drugs [13].…”
Section: The Quinoline Functional Groupmentioning
confidence: 92%
See 2 more Smart Citations
“…Quinoline anticonvulsant compounds. (Table 1), with TD50 values of greater than 300 mg/kg which was better than most of the market drugs [13].…”
Section: The Quinoline Functional Groupmentioning
confidence: 92%
“…Anticonvulsant activity was evaluated in the MES test, sc-Met test, and rotarod neurotoxicity test. The safest compound was 2 (Table 1), with TD 50 values of greater than 300 mg/kg which was better than most of the market drugs [13].…”
Section: The Quinoline Functional Groupmentioning
confidence: 96%
See 1 more Smart Citation
“…8 In the followed studies, we synthesized several [1,2,4]triazolo [4,3-a]quinoline derivatives and tested their anticonvulsant activities. We found that 1-substituted-7-benzyloxy-4,5-dihydro- [1,2,4]triazolo [4,3-a]quinolines, 9 7-alkoxyl-4,5-dihydro- [1,2,4]triazolo [4,3-a]quinolines 10 and 5-alkoxy- [1,2,4] triazolo [4,3-a]quinolines [In press] had significant anticonvulsant activities.…”
Section: Introductionmentioning
confidence: 99%
“…Compounds 3a -3o were prepared by the reaction of compounds 2a -2o with phosphorous pentasulfide in acetonitrile in the presence of triethylamine [15]. Since compound 2p (6-(2,4-dichlorobenzyloxy)quinoline-2-one) did not dissolve in acetonitrile, dioxane was used as solvent and compound 2p and phosphorous pentasulfide reacted in dioxane with stirring and refluxing for 24 h, which produced 3p (6-(2,4-dichloro-benzyloxy)-quinoline-2-thione) with a moderate yield.…”
Section: Introductionmentioning
confidence: 99%